Wide field imaging camera for CBERS 3&4 satellite series - Soares, Alexandre L.; Scaduto, Lucimara C.N.; Santos, Anderson R.; Dos Santos, Fabiano S.; Rebolho, Daniela C. [UNESP]; Segoria, Daniel M.; De Oliveira, André O.; Stefani, Mario A.; Maia, Herivaldo A.; Ferigoli, Gabriela; Augusto, André; Lima Netto, Custodio A.; et al. (Wiley, 2015)
The China-Brazil Earth Resources Satellites (CBERS) program is the result of a cooperation agreement established in 1988 between Brazil and China involving INPE (National Institute for Space Research) and CAST (Chinese Agency of Space Technology) to build remote sensing satellites. The purpose of this chapter is to describe the Wide Field Imaging Camera (WFI) of CBERS 3&4, which is the sensor with the largest swath width (866 km) and, consequently, the one that furnishes the lowest revisit time of five days of the four sensors in the payload module aboard the CBERS 3&4 satellites. It is an upgrade of the WFI camera aboard satellites of CBERS 1, 2 and 2B, and it has been entirely developed by a consortium formed by two Brazilian companies. The company Opto Eletrônica is in charge of designing and manufacturing the optical baffle and the optical channels, made up of the collecting lens, the focal plane, proximity electronics and the calibration system. Equatorial Sistemas is the company responsible for delivering of Ground Support Equipment (GSE), Signal Processing Electronics (SPE), and the mechanical support of the Opto-Electronic Block (OEB) on which the optical channels and the baffle are assembled.
Keywords: Charge-Coupled Device (CCD); China-Brazil Earth Resources Satellites (CBERS); Imaging sensor; Low Earth Orbit (LEO); Multispectral imager; Optics; Payload; Remote sensing; Satellite; Swath width